Troubleshooting Windows 2000 TCP/IP. - Syngress Media, Inc. (Rockland, Mass. : Syngress Media, 2000)
TCP/IP is a set of proposals developed to allow cooperating computers to share resources across a network. Some of the largest networks today are built on the TPC/IP protocol suite. Understanding how TCP/IP is "supposed" to work is not enough for today's network managers. In this book, readers will learn to prevent, detect, troubleshoot and correct TCP/IP network problems. By using products such as distributed sniffers, field metering tools and protocol analyses, network managers can learn a lot about what is going on in (or wrong in) an internetwork and be able to troubleshoot a live TPC/IP network. This book focuses specifically on identifying problem areas, including identifying and correcting protocol errors, DNS route problems, application faults and slow response times. Syngress have sold over 700,000 Microsoft and Cisco certification guides in the last two years. Most of the administrators buying these will be interested in this book. * TPC/IP is a very popular topic; readers will welcome a guide to troubleshooting and repairing problems * Tackles monitoring the network using protocol analyses * Teaches effective methods of baselining and trend analysis.
Discusses guidelines for planning, testing and implementing the setup, migration and connectivity problems of a Windows 2000 TCP/IP network.
Preface--TCP/IP overview--Setting up a Windows 2000 TCP/IP network--General Windows 2000 TCP/IP troubleshooting guidelines--Windows 2000 TCP/IP internals--Using network monitoring and troubleshooting tools in Windows 2000--Troubleshooting Windows 2000 NetBIOS name resolution problems--Troubleshooting Windows 2000 DNS problems--Troubleshooting Windows 2000 IP addressing problems--Troubleshooting remote access in a Windows 2000 TCP/IP network--Troubleshooting Windows 2000 connectivity problems at the network interface level--Troubleshooting Windows 2000 at the network internetwork level--Troubleshooting selected services on a Windows 2000 TCP/IP network--Windows 2000 TCP/IP fast track--Appendix A: TCP/IP troubleshooting secrets--Index.
Includes index (p.681-704).
Contributors: Debra Littlejohn Shinder (MCSE, MCP+I, MCT); Thomas W. Shinder (MCSE, MCP+I, MCT).
Forword: Ted Rohling.
Keywords: Microsoft Windows (Computer file).; TCP/IP (Computer network protocol); Computer networks -- Management; Operating systems -- Management; Electronic books